EFFECT OF DETENTION TIME IN REDUCING FE AND MN CONCENTRATION OF GROUNDWATER: CASE STUDY AT THE UNIVERSITAS NEGERI MALANG - Fadiyah Ghina Salsabila; Anie Yulistyorini; Husna Binti Takaijudin; Imam Alfianto (Universitas Trisakti, 2024)
Groundwater is a natural resource used by humans to fulfil their living needs which should meet the Republik Indonesia Minister of Health Regulation No. 2/2023. Aim: This research aims to contribute to solve these challenges and meet the clean water quality standard. Methodology and Results: The groundwater sample was taken from the deep well of Al-Hikmah Mosque, Universitas Negeri Malang (UM). It was indicated to contain Fe and Mn, as evidenced by its yellowish colour when left undisturbed for some time. A laboratory-scale experiment was conducted for the deep well treatment and analysis. The treatment system consists of aeration, sedimentation, and filtration. The filtration unit comprises several natural media such as gravel, silica sand, zeolite, and activated charcoal. This experiment used detention times of 120 and 240 minutes as dependent variables. Conclusion, significance, and impact study: The results showed that detention times of 120 and 240 min have efficiency on turbidity reduction of 92.86% and 98.69%, Total Dissolved Solids (TDS) of 10.42% and 14.47%, Fe of 23.01%, Mn of 62.39% and 94.70%, and for CaCO3 of 2.98% and 11.17%, respectively. The research findings demonstrated that a detention time of 240 min generated water quality that met the Minister of Health No. 2/2023 standards. Detention times of 120 minutes and 240 minutes led to significant differences in water quality concerning temperature and CaCO3. The filtration system with a detention time of 240 minutes can be considered as an alternative groundwater treatment solution for the deep well of Al-Hikmah Mosque, Universitas Negeri Malang.